High Performance FeNC and Mn-oxide/FeNC Layers for AEMFC Cathodes - Santori, Pietro Giovanni; Speck, Florian; Cherevko, Serhiy; Firouzjaie, Horie Adabi; Peng, Xiong; Mustain, William E.; Jaouen, Frederic (Journal of The Electrochemical Society, 2020)
While the Anion Exchange Membrane Fuel Cell (AEMFC) is gaining interest due to high power performance recently achieved with platinum-group-metal (PGM) catalysts, its implementation will require high-performing PGM-free cathodes. FeNC catalysts have shown high activity and stability for the Oxygen Reduction Reaction (ORR) in alkaline electrolyte; however, the production of hydrogen peroxide during ORR can lead to premature degradation of FeNC and ionomer. In order to minimize the amount of peroxide formed on FeNC,alpha-MnO2,beta-MnO2,delta-MnO(2)and alpha-Mn(2)O(3)were investigated as co-catalysts, with the aim of increasing the apparent activity of FeNC-based cathodes for the hydrogen peroxide reduction reaction (HPRR). The specific activity of alpha-Mn(2)O(3)for the HPRR was distinctly superior to the other Mn-oxides. The four Mn-oxides were mixed with a FeNC catalyst comprising atomically-dispersed FeN(x)sites, showing higher HPRR activity and higher four-electron ORR selectivity than FeNC alone. The stability of alpha-Mn2O3/FeNC was studiedoperandoby on-line inductively-coupled plasma mass spectrometry, to evaluate the potential and time dependent leaching of Mn and Fe. Finally, FeNC and alpha-Mn2O3/FeNC were applied at the cathode of AEMFCs, both achieving similar or higher current density at 0.9 V than a Pt/C commercial cathode, and peak power densities of ca. 1 Wcm(-2).
CRIS-Team WoS Importer:2020-10-16